Her impossible baby bombshell - Collins, Dani (Harlequin presents, 2021)
A life of hardship and crushing responsibility left billionaire Tsai Jun Li never wanting a child to suffer the same. He made sure he couldn't have children. So when Ivy Lam, the woman he shared one mesmerizing encounter with, appears claiming she's pregnant, he needs proof! After a painful relationship, Ivy's night with Jun Li was a magical fresh start. Now she's preparing for unexpected motherhood...but she didn't plan on being whisked away to Shanghai! Because it's suddenly clear Jun Li won't relinquish his claim ... to his baby or to Ivy!